Tree retention in cattle ranching systems partially preserves dung beetle diversity and functional groups in the semideciduous Atlantic forest : The role of microclimate and soil conditions - Gómez Cifuentes, Andrés Mauricio (2018)
Fil: Gómez Cifuentes, Andrés Mauricio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Nordeste; Argentina.